2017
DOI: 10.1115/1.4038464
|View full text |Cite
|
Sign up to set email alerts
|

Potential and Limitations of Dual Fuel Operation of High Speed Large Engines

Abstract: The aim of this paper is to identify and investigate the potential and limitations of diesel–gas combustion concepts for high speed large engines operated in gas mode with very small amounts of pilot fuel (<5% diesel fraction). Experimental tests were carried out on a flexible single cylinder research engine (displacement 6.24 dm3) equipped with a common rail system. Various engine configurations and operating parameters were varied and the effects on the combustion process were analyzed. The results presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Pilot injections with 1-2 % of full load fuel consumption is achievable, but is rather challenging for stable control. One of the most promising solution is installation of a separate pilot fuel nozzle (either integrated in one housing or installed as a separate fuel injector) [42,43,44]. Pilot fuel can be either injected directly into the (main) combustion chamber or in a pre-chamber.…”
Section: Low Pressure Dual Fuel Enginesmentioning
confidence: 99%
“…Pilot injections with 1-2 % of full load fuel consumption is achievable, but is rather challenging for stable control. One of the most promising solution is installation of a separate pilot fuel nozzle (either integrated in one housing or installed as a separate fuel injector) [42,43,44]. Pilot fuel can be either injected directly into the (main) combustion chamber or in a pre-chamber.…”
Section: Low Pressure Dual Fuel Enginesmentioning
confidence: 99%
“…This type of engine is operated by burning a premixed natural gas/air mixture ignited with a small amount of directly injected diesel fuel. This concept has several disadvantages, which are discussed in [5]. Nevertheless, dual-fuel engines are the subject of active research, and establishing an effective design process for dual-fuel engines and its fuel injection equipment represents a key priority.…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in advanced combustion concepts have focused on using two fuels of different propensities to autoignition to achieve high FCEs and ultra low NO x emissions [6][7][8]. These combustion concepts introduce a low reactivity fuel (e.g., natural gas or gasoline) through the intake manifold to create a premixed charge, which is compression-ignited using a high-pressure, high reactivity fuel spray (e.g., diesel) [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…These dual-fuel lowtemperature combustion (LTC) concepts, using natural gas, have immense potential to reduce CO 2 emissions; however, there is the added risk of "methane slip," i.e., any amount of unburned natural gas that escapes the tailpipe posing a risk. For example, if the engine-out methane emissions are greater than 0.1 g/bhp h, then they must be multiplied by a global warming potential factor of 34 [7]. A particular scenario of concern occurs at low engine loads where the coauthors and other researchers have observed instances of high engine-out unburned hydrocarbon (UHC) and carbon monoxide (CO) emissions and high cyclic combustion variations [10][11][12].…”
Section: Introductionmentioning
confidence: 99%